Multinomial Regression Analysis if Yam (Dioscorea Spp.) Consumers’ Preferences and Varietal Diversification Pattern in Nigeria - Achoja, Felix Odemero; Enujeke, Emmanuel Chukudinife; Ogisi, Oraye Dicta; Overehirha, Rebecca Tega (Asian Journal of Agriculture and Rural Development, 2020)
Multinomial regression analysis of yam consumers’ preference and varietal diversification in the yam production system in Nigeria was the thrust of this investigation. Five major yam farming communities were sampled randomly to get 200 respondents (suppliers and consumers) of yam. Parametric and non-parametric tests were employed to analyze the primary data collected with the questionnaire. The result indicates that white yam (Dioscorea rotundata) is the dominant variety among consuming households. The majority of the respondents prefer selling of white yam (76%) followed by water yam (13%) and yellow yam (l1%) in response to consumers’ preferences. The mean value of yam supplied was 505.34kg, while the mean quantity consumed was 14.56kg. The finding shows that the statistical relationship between the varieties consumed and supplied is strong and positive. It was concluded that as the demand-end is willing to purchase more quantity of white yam supplied, yam farmers and marketers are advised to scale-up production and supply respectively to take advantage of the increasing market demand for white yam in Nigeria. Also, more research works on yam varieties should be conducted by researchers to expand the value chain / industrial uses of other yam varieties to prevent their extinction.